Dietary reference values for thiamin. (19th December 2016) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Nowicka, Grażyna; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) derived dietary reference values (DRVs) for thiamin (vitamin B1). The Panel considers that data from depletion–repletion studies in adults on the amount of dietary thiamin intake associated with the erythrocyte transketolase activity coefficient (αETK) < 1.15, generally considered to reflect an adequate thiamin status, or with the restoration of normal (baseline) erythrocyte transketolase activity, without a sharp increase in urinary thiamin excretion, can be used to estimate thiamin requirement. In the absence of new scientific evidence, the Panel endorses the average requirement (AR) of 0.072 mg/MJ (0.3 mg/1, 000 kcal) for all adults proposed by the Scientific Committee for Food (SCF) in 1993 on the basis of one depletion–repletion study, in which both αETK and urinary thiamin excretion were measured. Results from other depletion–repletion studies are in agreement with this value. The Panel agrees on the coefficient of variation of 20% used by the SCF to cover uncertainties related to distribution of thiamin requirements in the general population, and endorses the population reference intake (PRI) of 0.1 mg/MJ (0.4 mg/1, 000 kcal) set by the SCF for all adults. The same AR and PRI as for adults, expressed in mg/MJ, are proposed for infants aged 7–11 months, children aged 1 to < 18 years, and during pregnancy and lactation, under the assumption that the relationship between thiamin requirement and energy requirement is the same in all population groups. Abstract : This publication is linked to the following EFSA Supporting Publications article:http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2016.EN-1138/full